The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2174/1874192401408010048
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Diabetes Care in Primary Health Centres in North Al-Batinah of Oman

Abstract: Objective: To assess the quality of diabetic care provided in primary health care settings in Oman.Methods: This was a cross-sectional study of randomly selected 500 patients with diabetes mellitus (DM) attending 6 primary care diabetic clinics in the north Al-Batinah region of Oman from January to December 2010. Nine standards on the quality of diabetes care were audited.Results: The mean age of the sample was 51±13 years, ranging from 15 to 87 years; the majority (61%) were females. The mean duration of DM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Approximately 463 million adults in the world live with diabetes mellitus (DM), and the number is estimated to reach 629 million by 2045 [ 1 ]. Diabetes is a rapidly increasing health problem in developing countries such as Oman [ 2 ]; in particular, type 2 diabetes (T2DM) is an emerging public health issue for the country [ 3 ]. The reported prevalence of diabetes among Omanis is 15.7% and, along with other chronic diseases, causes the death of 187.75 people per 100 thousand in Oman each year [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 463 million adults in the world live with diabetes mellitus (DM), and the number is estimated to reach 629 million by 2045 [ 1 ]. Diabetes is a rapidly increasing health problem in developing countries such as Oman [ 2 ]; in particular, type 2 diabetes (T2DM) is an emerging public health issue for the country [ 3 ]. The reported prevalence of diabetes among Omanis is 15.7% and, along with other chronic diseases, causes the death of 187.75 people per 100 thousand in Oman each year [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also one study in Nigeria showed that 96.4% of symptomatic (neuropathy) and 97.3% of asymptomatic patients with DM had never had foot examination [4]. Al-Shafaee and co-authors assessed nine standards on the quality of diabetes care in primary care diabetic clinics in the north Al--Batinah region of Oman and found that only 39% of the patients had foot examination [5]. Information about quite good implementation of best practice guidelines recommendations comes from Australian podiatrists study [6] but authors mentioned that the character of the study limits its interpretation.…”
Section: Introductionmentioning
confidence: 99%